EM FAVOR DOS POBRES: CONCEPÇÕES DE OPRESSÃO-LIBERTAÇÃO NA PEDAGOGIA FREIRIANA EM ARTICULAÇÃO COM O CRISTIANISMO DE LIBERTAÇÃO - Paixão, Claudia Ferreira da (2013)
The christianity of liberation can be considered a terminology to designate how actions of deliverance begins in matrix of christian religion catholic. In it, is implicit the concept of God is between people to provide experiences of deliverance of subject itself and in society. Procedural liberation that initiate liberating actions. Here, is more interesting action than faith. Think about christianity translate itself to think in salvific actions in oppressive situations. The faith that saves soul, but traps body, dont saved. The experiences spiritual devotionals, displaced of attitude of justice and love for the benefit of poor, passed through a difficult riddle of sense and social value in a concomitant historical period to emergence of theology of deliverance in Latina America. The church, in turn, condemned their best thinkers accusing them of unholy, because they cared too much about the social issue of subject-faithful. However, Christ himself prioritized save the social conditions of his followers. Christ thus gave emphasis to the subjects body. Your personal contact with his followers embody the truth of his words liberating. In that sense, one can say that Paulo Freire promoted a Christian education. A kind of liberation of poor mediated resource of word